Edukasi Literasi Keuangan Keluarga untuk Pengelolaan Konsumsi Rumah Tangga yang Efisien di Era Digital: Pengabdian - Sri Prilmayanti Awaluddin; Salim Sultan; Lilik Handayani; Sitti Hartini Rachman; Laode Muhammad Said Lutsfi Konstinia Djafar (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service program aims to enhance digital literacy among MSMEs in Warung Asem Batang Village as a strategy to improve local economic capacity in the digital era. The method used involves digital training sessions, mentoring, and practical implementation of social media and e-commerce for business promotion. The training activities demonstrated that the participants’ knowledge and skills in digital technology increased significantly, particularly in the use of smartphones, the creation of advertising content, and the use of digital platforms for marketing. Several participants were able to directly apply their learning by creating business profiles on social media, uploading promotional content, and making online sales. However, the program also encountered challenges such as limited access to digital infrastructure and varying participant abilities. These findings indicate that digital empowerment for MSMEs can be effectively implemented with a structured and contextual approach. Strengthening digital literacy among rural entrepreneurs is expected to drive inclusive and sustainable economic development.